The Effect Of Mind-Body-Spirit Therapy On Mood Score In Patients With Chronic Renal Failure With Hemodialysis - Cita, Errick Endra; Mizan, Dian Miftahul (STIKes Surya Mitra Husada, 2018)
Background: The number of new chronic renal failure patients with hemodialysis therapy continues to increase from year to year in Indonesia. When people learn they need to begin dialysis, they typically experience a flurry of emotions. The stress is caused by chronic illness accounts for a wide range of feelings and moods. This includes general irritability, anger and frustration over the problems caused by the illness, and feelings of being hopeless and helpless when faced with a life-threatening disease. Mind-body-spirit therapy (Concepts of Islam) focuses on the ability to manage the mindset and psychic that will affect the physical, attitudes and behavior of individuals in addressing their lives. Purpose : Giving mind-body-spirit therapy to hemodialysis patients to improve quality of life, given for 4 weeks with the frequency twice a week. Methods : Pre-experimental study with one group pre-test post-test. The sample of 23 patients with hemodialysis therapy taken by purposive sampling. The FACES test is a visual analog scale representation of mood was used in this study. Early screening on mood was taken in 23 patients (13 men and 10 women, mean age 51.5 years). Mind-body-spirit therapy (Islamic concept) consisted of Tausiyah (cognitive reconstruction), prayer, dhikr and drinking zam-zam water. The mood score was evaluated at week 4 after 4 weeks of treatments. Wilcoxon test results, obtained a significance value of 0,000 (p <0,05). This suggests